Debtors Prospective Assessment Application using Naive Bayes at Mitra Sejahtera Cooperative - Indra Griha Tofik Isa; Beni Junedi (STMIK Budi Darma, 2022)
Utilization of historical data into new knowledge can increase added value for its users, including Mitra Setia Cooperative (KMS) which has debtor data that is not utilized. “Not Paid Off” potentioal of debtors cannot be detected as early as possible. In this study using the Naive Bayes algorithm in classifying the feasibility of prospective debtors based on the classification of